Effect of the Program "Un paso activo" in the Movement Habits of Primary School Students - Álvarez Bogantes, Carlos (2018)
The purpose of this article was to evaluate the effect of the program “Un Paso Activo” on students’ physical activity of elementary students. Subjects: 69 third-grade students from a public urban school in the central canton of San José, of which 34 belonged to the experimental group (16 boys and 18 girls) and 35 to the control group (15 boys and 16 girls), with average ages Of 9.2 years, took part in the study. The intervention was led by the project coordinator and the institution’s physical education teacher, who provided the experimental group with a socio-constructivist approach to the lessons of Education given by the Ministry of Education in organizing the lessons of Physical Education, using the Active Step program as a methodological tool. Study Design: A quasiexperimental design was used over 4 months. Results: Boys and girls in the experimental group had a significant increase in knowledge, and in the time reported in physical activity through the directed report (<.05). Conclusions: The pedagogical strategy given by MEP improved the time spent on physical activity and the state of change of participants in the experimental group, especially in girls. This study proved to be practical and showed that it could be easily incorporated into the educational context.